A Study on Stylistic Characteristics of RohulArvah e Samaani on the Basis of Syntactic Structure and Rhetorical Features - سعید حاتمی; محسن نوبهاری (مطالعات زبانی و بلاغی)
Sadegh Hedayat is one of the first authors and researchers who has had a precise and scientific confrontation with vulgar culture of Iranians. He has used these elements in his stories while researching in vulgar culture and he has provided a clear image of the culture and traditions of his region. Stories of Sadegh Hedayat are an emerging point for many elements of vulgar culture as the most important part of his works, and are considered as cultural examples which by investigating and studying them, we can learn about cultural memoir of Iranians besides the cognition of their believes. In this paper, we are taking efforts to survey flashes of vulgar culture in the stories of Sadegh Hedayat and we are going to study the application method of these elements in stories of Hedayat. To achieve this objective, we have divided such elements in stories of Hedayat after proposing some discussions concerning vulgar culture and its inclusion and territory issues and we divided them into four categories of traditions and believes, vulgar poems and songs, proverbs and vulgar language. Then, by providing statistical tables we have studied application of these elements in stories of Hedayat.